The five-year survival of patients with various components of metabolic syndrome after Q-myocardial infarction - N. S. Mikhaylovska (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Introduction. According to clinical studies the presence of metabolic syndrome contributes significant increase in the level of early hospital mortality and impairs remote prognosis and survival of patients after myocardial infarction [5,6].The major danger represents summation of the various components of metabolic syndrome, as they provide a synergistic effect and form the pathogenetic cycle that leads to future fatal and non-fatal cardiovascular events [2]. Today the impact of the components of the metabolic syndrome on survival of patients after myocardial infarction has not been studied yet.